An analysis of the effects of marriage, divorce and death on the child maintenance obligation in South African law with some comparative perspectives - Clark, Brigitte (Rhodes University, Faculty of Law, Law, 2000)
This thesis analyses the law of child maintenance in South Africa with particular reference to the effects of marriage, death and divorce on such an obligation. In the introductory section, the types of South African family are demographically and statistically sketched, from a socio-legal perspective with some reliance on interdisciplinary research to assess the prevalence of the AID/HIV epidemic in South Africa, and the effects of poverty and ageing on the incidence of marriage and death. In the second part of the thesis, the parental child maintenance obligation is analysed in the common law context. The effects of serial marriage and arificial conception are also analysed with regard to their effect on the concept of biological parent. The nature and definition of parenthood is examined and the diverse and fluid nature of parenthood in South African society is stressed, particularly in relation to children's welfare. One of the aims of the thesis is to indicate how parenthood refers to a fluid set of social practices which are both biologically and culturally situated and thus have a complex effect on the maintenance obligation. The procedural problems of enforcement are also analysed in the light of recent amendments to the law in terms of the Maintenance Act 99 of 1998 (not yet in force) and some further proposals for reform in this area are proposed. The third part of the thesis examines the state obligation to maintain children, especially in the light of the state's commitments to children in terms of the Constitution of the Republic of South Africa Act (l08 of 1996) and its international commitments in terms of the United Nations Convention on the Rights of the Child which was ratified by the South African government on 16 June 1995. In the fourth part of the thesis, there is some comparative analysis, firstly, of the procedural law reforms proposed in Namibia as a result of detailed research done there. Secondly, alternative methods of assessing and enforcing child maintenance obligations in Australia and England are examined and briefly assessed in relation to their possible implementation and efficacy in a South African context. Finally, the thesis concludes with an overall synopsis of the position in this country and some proposals for reform in the light of the international and constitutional commitments of the state.
Keywords: Child support -- Law and legislation -- South Africa; Divorce -- South Africa; Marriage -- South Africa; Death